Islamic Religious Education Program Evaluation in High Schools: Assessing Student Engagement and Curriculum Effectiveness - Atthallah; Olivia Safana (International Journal of Curriculum Development, Teaching and Learning Innovation, 2024)
This research evaluates the effectiveness and impact of the Islamic Religious Education (IRE) Program in high schools, focusing on its influence on students' religious knowledge, values, and attitudes. A mixed-method approach was employed, combining quantitative surveys with qualitative interviews and observations. The evaluation revealed strong student engagement and participation in the program, with positive impacts on religious knowledge and values. Pedagogical approaches such as cooperative learning and multimedia resources were effective in enhancing students' learning experiences. However, opportunities for improvement were identified in curriculum content, teacher competence, and community engagement. These findings have critical implications for policy development, educational practice, and future research in Islamic religious education. By addressing these implications, stakeholders can work towards enhancing the quality, relevance, and inclusivity of religious education programs, ultimately fostering students' holistic development within the Islamic tradition.